Evaluasi Laju Pertumbuhan, Keragaman Genetik Dan Estimasi Heterosis pada Persilangan Antar Spesies Ikan Patin (Pangasius sp.) - Didik Ariyanto; Retna Utami (Universitas Gadjah Mada, 2006)
Thai catfish (Pangasius sp.) is one of the most popular cultured catfish in Indonesia. There are 2 species Thai catfish i.e. P. hypopthalmus which introduced from Thailand in 1972 and P. djambal an endogenous Indonesian fish. The aims of this research were to evaluate the growth rate, genetic variability and heterosis estimacy on interspecific crossing of these species. The result showed that the growth rate of F1 P. hypopthalmus X P. djambal was better than its parents. Genetic variability of P. hypopthalmus, P. djambal and their hybrids were 12.54, 12.38, and 27.02, respectively, and heterosis estimacy of their hybrids on growth (length and weight) were in high categories about 48.98-257.90%.